Leisure‐time and occupational physical activity demonstrate divergent associations with periodontitis: A population‐based study. (22nd January 2023) - Marruganti, Crystal; Baima, Giacomo; Grandini, Simone; Graziani, Filippo; Aimetti, Mario; Sanz, Mariano; Romandini, Mario
Abstract: Aim: To evaluate the association between leisure‐time/occupational physical activity (LTPA/OPA) and periodontitis in a nationally representative sample of the U.S. population. Materials and Methods: Data from 10, 679 adults were retrieved from NHANES 2009–2014 database. Physical activity was assessed through the Global Physical Activity Questionnaire, and accordingly, subjects were classified as performing either high or low LTPA/OPA. Periodontal status was assessed through a full‐mouth periodontal examination, and subjects were classified according to the AAP/CDC criteria (no, mild, moderate, or severe periodontitis). Simple and multiple regression analyses were applied to study the association between LTPA/OPA and periodontitis/severe periodontitis. Results: Multiple regression analyses identified high LTPA as a protective indicator for periodontitis (odds ratio [OR] = 0.81; 95% confidence interval [CI]: 0.72–0.92), while high OPA was found to be a significant risk indicator (OR = 1.16; 95% CI: 1.04–1.30). The combination low LTPA/high OPA showed a cumulative independent association with periodontitis (OR = 1.47; 95% CI: 1.26–1.72). Moreover, both high LTPA (OR = 0.72; 95% CI: 0.58–0.90) and high OPA (OR = 1.29; 95% CI: 1.09–1.53) were significantly associated with stronger estimates of severe periodontitis; the same was observed for the combination of low LTPA/high OPA (OR = 1.66; 95% CI: 1.29–2.15). Conclusions: LTPA and OPA showed divergent associations with periodontitis.